Super-infection by multiple microorganisms in COVID-19 patients - Gomez, Andrea C.; Ortiz, Tamin; Valenzuela, Angélica; Egoávil-Espejo, Rocío; Huerto-Huanuco, Rosario; Pinto, Joseph A.; Lagos, Jose; Ruiz, Joaquim (Frontiers in Molecular Biosciences, 2023)
This study aimed to describe the clinical characteristics of patients with COVID-19 coinfected with multiple multidrug resistant bacteria. Patients hospitalized in the AUNA network between January and May 2021, diagnosed with COVID-19 and at least 2 other infecting microorganisms, were retrospectively included in the analysis. Clinical and epidemiological data were extracted from clinical records. The susceptibility levels of the microorganism were determined using automated methods. Antibiotic resistance was established among infecting bacteria accounting for ≥5 isolates. Twenty-seven patients (21 men and 6 females) accomplished inclusion criteria, with a maximum of eight co-infecting bacteria or fungi during admission time. Seven patients (25.9%) died, with a higher but not significant lethality among women (50% vs 19.0%). Fifteen patients presented at least one established comorbidity, with hypertension being the most frequent. The time elapsed between COVID-19 diagnosis and hospital attendance was 7.0 days, with that of patients with a fatal outcome being longer than that of alive patients (10.6 vs. 5.4). Up to 20 different microorganisms were isolated, with Pseudomonas aeruginosa being the most common (34 isolates). In general, antibiotic resistance levels were high, especially in Acinetobacter baumannii isolates, with resistance levels of 88.9% to all antimicrobial agents tested except colistin (0%). In conclusion, the present results show the presence of multiple microorganisms that co-infect COVID-19 patients. While fatal outcome rates are in the range of other reports, the presence of a series of multidrug resistant microorganisms is of concern, showing the need to reinforce control measures to limit the expansion of almost untreatable microorganisms.